Cardiovascular Risk Profile on the Island of Santiago—Cabo Verde (PrevCardio.CV Study) - Francisco Rodrigues; Kelly Mascarenhas; Júlio Rodrigues; Patrícia Coelho (Life, 2024)
Cerebrocardiovascular diseases are a major global public health concern, significantly impacting morbidity, mortality, and posing substantial socio-economic challenges. In Cabo Verde, non-communicable diseases have become the leading causes of morbidity and mortality. This study aimed to estimate the prevalence of risk factors for cerebrocardiovascular diseases and their association with cardiac electrical alterations in adults on Santiago Island, Cabo Verde. A cross-sectional population-based study using simple random sampling was conducted on individuals over 18 years of age. The sample size of 599 was based on Santiago Island’s 2021 population projection. Data collection occurred in October and November 2021, involving questionnaires on risk factors and cerebrocardiovascular diseases; blood pressure assessments; and capillary blood glucose measurements. The sample was predominantly female, with the 18–27 age group being the largest. Key risk factors included physical inactivity (65.1%), BMI ≥ 25 kg/m2 (42.6%), hypertension (32.6%), and family history of cerebrocardiovascular diseases (19.9%). Other factors were alcoholism (14.4%), hypercholesterolemia (8.3%), smoking (7.3%), diabetes (4.5%), and hypertriglyceridemia (1.3%). Notably, 9.3% had no risk factors, 27.5% had one, 36.2% had two, and 26.9% had three or more. There is a high prevalence of risk factors for cerebrocardiovascular diseases on Santiago Island, particularly among females.